2021
DOI: 10.3389/fimmu.2020.584808
|View full text |Cite
|
Sign up to set email alerts
|

Immune Responses to Gram-Negative Bacteria in Hemolymph of the Chinese Horseshoe Crab, Tachypleus tridentatus

Abstract: Chinese horseshoe crab, Tachypleus tridentatus, is an ancient marine arthropod with a long evolutionary history. As a kind of living fossil species, the pathogen defenses of horseshoe crabs entirely depend on the innate immune system. Although, there are abundant immune molecules found in the horseshoe crab hemolymph, the biological mechanisms underlying their abilities of distinguishing and defending against invading microbes are still unclear. In this study, we used high-throughput sequencing at mRNA and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 50 publications
(62 reference statements)
3
23
1
Order By: Relevance
“…In the previous study, we performed a multi-omics (transcriptome and peptidome) analysis of Chinese horseshoe crab hemolymph to identify genes induced by bacterial infection and found that the gene, termed Tatritin in this study, was significantly ( p < 0.05) induced by pathogenic V. parahaemolyticus ( 29 ). The open reading frame (ORF) and 3′ UTR sequences of Tatritin (accession number OM128176) were identified via RT-PCR.…”
Section: Resultsmentioning
confidence: 72%
See 4 more Smart Citations
“…In the previous study, we performed a multi-omics (transcriptome and peptidome) analysis of Chinese horseshoe crab hemolymph to identify genes induced by bacterial infection and found that the gene, termed Tatritin in this study, was significantly ( p < 0.05) induced by pathogenic V. parahaemolyticus ( 29 ). The open reading frame (ORF) and 3′ UTR sequences of Tatritin (accession number OM128176) were identified via RT-PCR.…”
Section: Resultsmentioning
confidence: 72%
“…The antimicrobial peptide named Tatritin was newly identified from the transcriptome of Chinese horseshoe crab ( 29 ) and showed a significantly upregulated expression ( p < 0.05) in hemolymph of Chinese horseshoe crab after infection with Gram-negative bacteria. The Tatritin gene consists of three exons, coding 68 amino acid residues.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations